SAT0207 Correlation of clinical, serologic and histologic findings in a large cohort of primary sjögren's syndrome patients: A multicentric cross-sectional study. (23rd January 2014) - Baldini, C.; Pepe, P.; Quartuccio, L.; Priori, R.; Bartoloni Bocci, E.; Alunno, A.; Colafrancesco, S.; Gattamelata, A.; Maset, M.; Modesti, M.; Tavoni, A.; De Vita, S.; et al.
Abstract : Background: Although primary Sjögren's syndrome (pSS) is often a benign condition some patients develop systemic features. Identifying independent risk factors for pSS different clinical phenotypes would provide useful insights into patients' assessment. Objectives: to describe the clinical presentation of pSS in a large cohort of patients and to identify independent risk factors for severe disease manifestations. Methods: Cumulative demographic, clinical, serological, histological and therapeutic data of 1115 pSS patients were retrospectively evaluated. Independent risk factors for disease manifestations were identified by logistic regression. Results: The cohort included 1115 (1067 F:48M) pSS patients with a mean age of 51.6±13.8 yrs at diagnosis and 57.5±13.7 yrs at inclusion in the study (mean follow-up=5.8±6.5 yrs). Anti-Ro/SSA and anti-La SSB were detected in the 68% and 37% of the cases. Xerostomia (92%), xerophtalmia (94%) and articular involvement (61%) were the most commonly detected clinical manifestations. Salivary gland enlargement was detected in 346/1115 (31%) pSS patients while 475/1115 (42%) developed systemic extra-glandular involvement. Moderate to severe leukopenia (28%), peripheral arthritis (11%) and sensory-motor neuropathy (1.8%) were the most severe disease extra-glandular manifestations requiring immunosuppressive drugs. Independent risk factors for leukopenia were Raynaud's phenomenon (RP) (p=0.008), low C3 (p=0.001), hypergammaglobulinemia (p=0.0006) and cryoglobulinemia (p=0.01). Arthritis was associated to RP (p=0.005) while sensory-motor neuropathy to purpura (p<0.0001), low C4 (p<0.0001) and cryoglobulinemia (p<0.0001). From the analysis, low C3/C4, hypergammaglobulinemia and cryoglobulinemia emerged as prognostic adverse laboratory abnormalities. Table 1 summarises patients' clinical presentation according to the number of the laboratory abnormalities detected ("group A" = no abnormalities, "group B" =1 and "group C" ≥2 abnormalities). Conclusions: This study described the presentation of pSS in a large cohort of patients allowing us to identify independent risk factors which might help to predict the signs and symptoms of the disease. Patients with laboratory signs of B-cell hyperactivation should be more closely monitored since they may be at higher risk of severe extra-glandular involvement. Disclosure of Interest: None Declared